From legal to illegal workers: the process and challenges in recruiting Indonesian migrants workers in Sabah, East Malaysia - Dayang Suria Mulia; Ramlah Daud; Wan Shawaluddin Wan Hassan (Penerbit UM, 2015)
According to the statistics in 2010, there are about 1.3 million documented migrant workers in Malaysia with the largest number (approximately 1 million) coming from Indonesia. By entering the country legally using legal documents, these workers will be protected by the employment laws and regulations, covered by medical insurance, obtaining work permits, and monitored by the Indonesian Consulate in Malaysia. This paper investigates the roles of recruiting agencies in Sabah, East Malaysia particularly those who are involved directly in recruiting new workers from Indonesia. Specifically, it explores what the strategies utilized and challenges that are encountered by the agencies in the process of recruiting new workers from Indonesia are. The issue of why migrant workers from Indonesia are still entering this country as undocumented workers despite continuous effort to recruit them legally is expounded in this paper. This study incorporates The New Economics of Labour Migration Theory (NELM). Data collection is based on a qualitative method. Twenty registered agents in Sabah and government agencies including Federal Land Consolidation and Rehabilitation Authority (FELCRA) and Sabah Rubber Industry Board (SRIB) as well as Indonesian Consulate were interviewed. The findings suggest that among the challenges in recruiting new migrant workers from Indonesia are the slowness of bureaucratic process and the overlapping roles of various government agencies such as Department of Immigration, Labour Department, Human Resources Department and GroWarisan as a ‘gatekeeper.’ The process of recruiting new workers takes at least three to six months. The agencies are also facing challenges to attract new workers due to low wages offered by the economic sectors such as palm oil plantation. Therefore, economic sectors such as agriculture, construction, manufacturing, and services sectors are still facing labour shortages.